College Party Culture and Sexual Assault - Jason M. Lindo; Peter Siminski; Isaac D. Swensen (Institute for the Study of Labor (IZA), 2016)
This paper considers the degree to which events that intensify partying increase sexual assault. Estimates are based on panel data from campus and local law-enforcement agencies and an identification strategy that exploits plausibly random variation in the timing of Division 1 football games. The estimates indicate that these events increase daily reports of rape with 17-24 year old victims by 28 percent. The effects are driven largely by 17-24 year old offenders and by offenders unknown to the victim, but we also find significant effects on incidents involving offenders of other ages and on incidents involving offenders known to the victim.
Keywords: I23; K42; 330; sexual assault; rape; college; alcohol; football